Ruptured solid pseudopapillary neoplasm in children: a 20-year single-center experience - Ha, Suhyeon; Jeong, Soo-Min; Kwon, Hyunhee; Namgoong, Jung-Man (Frontiers in Pediatrics, 2026)
PurposeSolid pseudopapillary neoplasm (SPN) is a rare pancreatic tumor with an excellent prognosis after resection. Tumor rupture is uncommon and may increase the risk of peritoneal spread, but data in children are extremely limited. This study evaluated clinicopathologic features, operative outcomes, and recurrence patterns in ruptured SPN in children over 20 years.MethodsWe retrospectively reviewed seven children (<18 years) with histologically confirmed ruptured SPN who underwent resection at a tertiary center between 2004 and 2024. Clinicopathologic, operative, and follow-up data were analyzed. Recurrence was categorized as suspected (radiologic) or confirmed (histologic).ResultsAll patients were female (median age 12 years). Median tumor size was 7.4 cm, mostly arising from the pancreatic body or tail. Rupture was spontaneous in 42.9% and trauma-related in 57.1%; no iatrogenic rupture events occurred. Distal pancreatectomy was performed in 71.4%. Suspected recurrence occurred in five patients (71.4%), during a median follow-up of 47 months; however, confirmed recurrence was identified in two (28.6%), both with peritoneal dissemination. Both confirmed recurrence cases involved tumors larger than 10 cm with peripancreatic soft tissue extension, although no statistical associations can be inferred due to the small sample size.ConclusionRuptured SPN in children carries a measurable risk of true peritoneal recurrence, but radiologic findings may overestimate relapse. Tumor size and peripancreatic extension may help stratify recurrence risk. Complete resection, thorough peritoneal assessment, and long-term surveillance are essential. Multicenter studies are needed to refine management strategies.